PENCEGAHAN STUNTING MELALUI PENYULUHAN PADA IBU HAMIL DI PUSKESMAS BANDAR AGUNG, LAMPUNG TENGAH - Sadiman, Sadiman; Yuliawati, Yuliawati; Widiyanti, Septi (MAJU : Indonesian Journal of Community Empowerment, 2024)
Stunting is a global problem, the incidence in the world in 2020 in toddlers is 149.2 million in the world with the highest incidence in Africa 31.7%. In Lampung Province in 2018 the stunting case was 27.28%. Stunting can inhibit the development of intelligence and motor skills and short-term physical growth failure. The method of implementing Community Service is in the form of counseling about stunting which includes: Pretest, counseling with lectures and questions and answers, discussion and posttest. The results showed an increase in the average value of pregnant women's knowledge about stunting pretest 10.867 to 14.067, and there was an influence of pocket book media on pregnant women's knowledge about stunting with a p-value of 0.001. Suggestions for the need for ongoing counseling and pocket books can be a medium for education about stunting in community services.